T-stub behaviour under out-of-plane bending. I: Experimental research and finite element modelling. (1st September 2015) - Gil, Beatriz; Goñi, Rufino
Highlights: Connections under loads in the beam minor axis direction are usually considered as pinned or rigid. An experimental program consisting of five T-stub under out-of-plane bending has been carried out. FE models have been validated with the experimental results. The connection characteristics have been obtained by means of tests and FEM. Comparison with the limits of EC3 probes that the studied connections are semi-rigid and partial strength. Abstract: Beam to column connections subjected to loads in the beam minor axis direction are usually considered either as pinned or rigid for both resistance and stiffness checks. However, modern codes contemplate the possibility of semi-rigid and partial strength connections. The Eurocode 3 provides criteria, based on the component method, to characterise such connections. There are unresolved issues regarding three-dimensional connections and connections subjected to out-of-plane effects that need further research. Their behaviour relies mainly on the characterisation of the components acting on the T-stub under out-of-plane bending, and this characterisation is the aim of this paper. An experimental program consisting of five T-stub tests has been carried out and finite element models have been developed. The finite element models have been validated with the experimental results and prove to be an accurate tool for the characterisation of 3D connections. The connection characteristics have been obtained by means of tests and finite element models, and after comparison with the limits provided by the Eurocode 3, it is concluded that all connections under study are indeed semi-rigid and partial strength.